(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2015)
The idioms with the meaning of ’very, excessively, above all measures, many’ are analyzed in the article. Their differentiation in usage, depending on the selected images, components-lexemes and highly expressed assessment of carrying additional national cultural information, was examined.